2017
DOI: 10.7475/kjan.2017.29.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward One's Own Aging among Korean Middle-aged Adults and the Elderly

Abstract: Purpose:The purpose of this study was to identify and compare the factors influencing attitude toward one's own aging among Korean middle-aged adults and the elderly. Methods: A cross sectional study was performed with a total sample of 70 middle-aged adults and 64 elderly reside in two metropolitan areas. Data were collected from August 2015 to November 2015 using the Perceived Health Status Scale, the Health Locus of Control Scale and the Attitude Toward own Aging (ATOA) Scale. The statistics used include pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…43−47 This association, however, might be more complex given the interdependence between family members. In South Korea, for example, research has found a tendency towards negative self-perceptions of aging among older people, 48,49 with both intergenerational and spousal relations and contexts (including health status) being associated with one's self-perceptions of aging, thus, stressing the interdependence between family members. 50 There also are variations in self-perceptions of aging across different age cohorts, with younger Japanese cohorts reporting better self-perceptions of aging compared with older cohorts, 47 as well as variations across geographic areas, with rural Chinese older adults reporting poorer self-perceptions of aging.…”
Section: Ageism and Filial Piety In The Western Pacific Regionmentioning
confidence: 99%
“…43−47 This association, however, might be more complex given the interdependence between family members. In South Korea, for example, research has found a tendency towards negative self-perceptions of aging among older people, 48,49 with both intergenerational and spousal relations and contexts (including health status) being associated with one's self-perceptions of aging, thus, stressing the interdependence between family members. 50 There also are variations in self-perceptions of aging across different age cohorts, with younger Japanese cohorts reporting better self-perceptions of aging compared with older cohorts, 47 as well as variations across geographic areas, with rural Chinese older adults reporting poorer self-perceptions of aging.…”
Section: Ageism and Filial Piety In The Western Pacific Regionmentioning
confidence: 99%
“…First of all, in order to improve the healthy aging of older adults in Korea, it would be needed to understand its degree and then to analyze the variables related to it. However, the research on the health of older adults in the nursing aspect has been limited to the concept of attitude towards aging [7], life satisfaction [8], quality of life, health-related quality of life, successful aging, and health conservation [9][10][11][12], while there are not many studies on healthy aging [13]. Especially, a study on healthy aging was conducted a long time ago when the environment was quite different from the recent environment [13], and it did not clearly divide older adults, so it needs to be analyzed more systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, family visits to the nursing homes greatly aids in the lowering of the stress levels of elderly and the plays healing roles in their mental and physical state (Choi, Ransom, & Wyllie, 2008). It is not an exaggeration to state that the elderly consider their family to become increasing valuable and important as time goes on (Jo, 2006). Despite all these barriers and negative feelings for the nursing homes, many elderly people were willing to stay and work it out if it meant helping their families and not creating more burden for them.…”
Section: Discussionmentioning
confidence: 99%